Risk Factors of Pulmonary Obstruction Among Textile Industry Workers - Sumardiyono, Sumardiyono; Widjanarti, Maria Paskanita; Suratna, Farhana Syahrotun Nisa; Ismayenti, Lusi; Rinawati, Seviana; Atmojo, Tutug Bolet; Rha, Warda Yussy; Gustav, Jordan Syah; Utomo, Bekti; Wijayanti, Reni; Chahyadhi, Bachtiar (Media Publikasi Cendekia Indonesia, 2025)
Chronic exposure to cotton dust in the textile manufacturing industry has been a possible risk factor for pulmonary obstruction. Not many studies, however, have investigated its impact in combination with personal variables like age, gender, and length of service, particularly in developing countries. The present study investigated the impact of cotton dust exposure, age, gender, and length of service on the incidence of pulmonary obstruction among textile workers in Surakarta, Indonesia. Observational analytic study using cross-sectional design was done on 88 eligible workers. Quantitation of exposure to cotton dust was done with a High-Volume Air Sampler and lung function ascertained using spirometry. Data analysis was done through simple and multiple binary logistic regression at a significance level of 0.05. The incidence of pulmonary obstruction was 56.8%. Being exposed to cotton dust levels exceeding the threshold limit value (TLV) of 0.2 mg/m³ significantly increased the risk of pulmonary obstruction (OR: 4.18; 95% CI: 1.51–11.63; p=0.006). Employment duration was also significantly associated with pulmonary obstruction (OR: 1.21 per year; 95% CI: 1.03–1.44; p=0.023), while age and gender were not significant predictors. The accuracy of the final model was 75%, which is considered to be acceptable in occupational health studies in predictive modeling. The current research reaffirms that long-term exposure to cotton dust and extended working hours are critical risk factors for pulmonary obstruction in textile industry workers. Therefore, it is recommended to long-working-hour employees to have proper control of the exposure and continuous lung function monitoring.